Belajar Membaca Al-Quran Dengan Metode Qiroati Di KB Mutiara Insani - Hasan Hasan (LPPM STAI Diniyah Pekanbaru, 2020)
This journal aims to provide an overview of learning to read the Qur'an with the Qiroati method carried out at KB Mutiara Insani. This research is a qualitative descriptive study with a percentage. The results of the study were divided into two categories: individual and institutional achievements: Individually: 15 students were only able to reach volume 2 with a mastery level of 33%, 8 KB Mutiara Insani students were only able to volume 3 with a mastery level of 50%, 2 KB Mutiara Insani learners are able to reach volume 4 with a mastery level of 66%, 6 KB Mutiara Insani learners are able to volume 5 with a mastery level of 83%, 10 KB Mutiara Insami learners are able to read the Qur'an until volume 6 (up to the Qur'an) with a level of mastery of 100% with the category of Very Good. As for the target of achieving mastery at the institutional level (KB. Mutiara Insani) 61.59% with the category Less.